Analgesic efficacy and safety of Duloxetine premedication in patients undergoing hysterectomy - Tabinda Qamar; Amna Khan; Farial Mehmood Dar; Faiza Gull; Muzaffar Shah Umair; Aiman Shah (Medical Journal of South Punjab, 2024)
Objective: to evaluate the effect of Duloxetine on postoperative pain management in patients who underwent hysterectomy, researchers conducted a study to assess the drug's efficacy and its impact on pain levels following the surgical procedure.Methodology: Study was prospective cohort conducted at Nishtar Hospital, Multan from March 2023 to February 2024. The study included undergoing abdominal hysterectomy for conditions such as endometriosis, ovarian or cervix cancer, fibroids, or abnormal vaginal bleeding after failed alternative treatments. Postoperative pain was assessed with VAS every 15 mins for 45 mins in recovery, then at 2, 4, and 24 hours. Pethidine (25 mg IV) was given for VAS > 4, along with acetaminophen (1 g IV every 6 hours). QOR-40 scores were assessed after 24 hours. Adverse effects of DLX were monitored. Vital signs were checked at specific intervals throughout the perioperative period.Results: The mean pain score at recovery for Duloxetine group was less than Placebo group as 3.11±0.88 and 9.94±1.04, respectively. (p